Effectiveness of skipping exercises and bench step-up againts explosive power leg muscles - Hidayat, Arif; Pratama, Riyan; Hardiyono, Bayu (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2020)
The purpose of this study is to determine whether there are differences in the skipping exercises and the bench step-up on the leg muscle explosive power of members of Participants of extracurricular futsal Bina Darma. The research method used an experimental method with a two-group pretest-posttest design, a population of 24 people, and a sample of 12 people in the skipping exercise group and 12 in the bench step-up exercise group using the MSOP technique. The pre-test and post-test test instruments used a standing broad jump. Data analysis used t-test difference (paired t-test). The results showed a significant difference in skipping exercises and the bench step-up in generating leg muscle explosive power in Bina Darma university futsal club participants (F-count 4,620> F-table 3,98). The percentage of skipping training on the explosive power of the leg muscles was 26%, and bench step-up training was 63%, so the difference between the two was 37%. Still, it was inseparable from the limitations that existed during the study, namely: 1) The sample was not in a dormitory, so there might be some who practiced alone outside treatment 2) In this study, the subjects studied were still very few, limited to the men's futsal extracurricular members of Bina Darma University Student Activity Unit. 3) The researcher cannot control other factors that may affect the test results, such as body condition, psychological factors, and so on. Suggestions for the trainer or teacher; they should provide more varied exercises as an effort to increase the explosive power of the leg muscles and further research is needed by adding other variables.